Tylieji priesaikos riteriai : Lietuvos pasiuntinybė Vašingtone Šaltojo karo metais Quiet knights of the oath : The Lithuanian Embassy in Washington during the Cold War - Petraitytė-Briedienė, Asta (Vytautas Magnus University, 2014)
The Lithuanian Embassy in Washington during the Cold War, Lithuanian diplomats Povilas Žadeikis, Stasys Antanas Bačkis, Juozas Kajeckas, Stasys Lozoraitis (junior): activities and characteristic, diplomats relations with Lithuanian diaspora in USA, The Lithuanian Embassy in Washington's contact with the State Departments of US, The Embassy relations and cooperation with the Latvian and Estonian diplomatic corps, an "invisible network".